Effect of Ovariectomy on Fas Expression in Endometrial Epithelial Cells in White Rats (Rattus norvegicus) - Fitriasnani, Meirna Eka; Lutfi, Erik Irham (STRADA : Jurnal Ilmiah Kesehatan, 2021)
One method to make menopause in experimental animals is the ovariectomy method. During menopause, hormonal changes occur, namely a decrease in the hormone estrogen. Estrogen is a powerful antioxidant that protects against oxidative stress during reproduction. The purpose of this study is to prove that ovariectomy can increase the expression of endometrial epithelial cells in white rats (Rattus norvegicus). This research design is true experimental with a randomized post- only control group design. The experimental animals used were female white rats (Rattus norvegicus) aged 9-12 weeks with a bodyweight of 150-250 grams totaling 30 individuals which were divided into 2 groups, namely the negative control group and the positive control group. Ovariectomy was performed and waited until the 28th post ovariectomy day. The apoptotic index was examined using Tunnel Assay. The data were analyzed and the Independent Sample T - Test was conducted